Tri-generative Stochastic Model of Population Growth - Nigam, Rahul (JOURNAL OF ADVANCES IN MATHEMATICS, 2015)
This paper investigates the population growth of a certain species in which every generation reproduces twice. First we probe the cases of 100% regeneration. We find that the population stabilizes for all the case although the stable values are different and exhibit interesting patterns. Then we study the survival period of a species by randomizing the reproduction probabilities within a window at same predefined ages. Now the population meets three different possibilities when left over for long periods -Dies, Stabilizes, Shoots up. We carry out a detail study for these outcomes in the parameter space defined by the reproduction probabilities.